List decoding of rank-metric and cover-metric codes - Liu, Shu (2018)
A fundamental challenge in coding theory is to efficiently decode the original transmitted message even when a few symbols of the received word are erroneous. Traditionally, unique decoding outputs a unique codeword and can only correct up to half the minimum distance of the code. An alternative notion of decoding called list decoding allows the decoder to output a list of all codewords and permits recovery from errors well beyond the unique decoding barrier. However, the study of list decoding of rank-metric and cover-metric codes has not been as extensive and complete as that of Hamming metric codes.